CONFIGURATION OF CONTENT MATERIALS ON REGIONAL REGULATIONS ON REGIONAL RESEARCH : KONFIGURASI MATERI MUATAN PERATURAN DAERAH TENTANG RISET DI DAERAH - Rudi Wijaya; Eko Raharjo; Rika Septiana (Constitutional Law Society, 2022)
The strengthening of the national research system after the promulgation of Law Number 11 of 2019 concerning the National System of Science and Technology (UU Sisnas Science and Technology) requires that the research and innovation system be strengthened in the regions. Legal instruments in the form of regional regulations have an urgency to ensure the sustainability of the research and innovation ecosystem and are also strengthened in the regions. Therefore, the content of regional regulations on research needs to be well formulated so that the content material is not only a copy of the National Science and Technology Law but can adapt to regional conditions, needs, and ongoing conditions.